2022
DOI: 10.1038/s41598-022-08478-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional biphenylene: a promising anchoring material for lithium-sulfur batteries

Abstract: Trapping lithium polysulfides (LiPSs) on a material effectively suppresses the shuttle effect and enhances the cycling stability of Li–S batteries. For the first time, we advocate a recently synthesized two-dimensional material, biphenylene, as an anchoring material for the lithium-sulfur battery. The density functional theory calculations show that LiPSs bind with pristine biphenylene insubstantially with binding energy ranging from −0.21 eV to −1.22 eV. However, defect engineering through a single C atom vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Beyond graphene dominated by the periodic hexagonal rings, several carbon allotropes composed of hybrid carbon rings have been recently predicted by first-principles calculations or synthesized experimentally. [22][23][24][25][26][27][28] Biphenylene, as a novel 2D carbon material consisting of four-(C 4 ), six-(C 6 ) and eight-membered (C 8 ) carbon rings, shows great potential in applications such as catalysis, 29,30 batteries, 31 sensors, [32][33][34] etc. The hybrid carbon rings at the biphenylene monolayer surface introduce non-equivalent carbon sites and improve the interfacial activity, such that the biphenylene monolayer can be easily oxidized and shows more active carbon sites for chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond graphene dominated by the periodic hexagonal rings, several carbon allotropes composed of hybrid carbon rings have been recently predicted by first-principles calculations or synthesized experimentally. [22][23][24][25][26][27][28] Biphenylene, as a novel 2D carbon material consisting of four-(C 4 ), six-(C 6 ) and eight-membered (C 8 ) carbon rings, shows great potential in applications such as catalysis, 29,30 batteries, 31 sensors, [32][33][34] etc. The hybrid carbon rings at the biphenylene monolayer surface introduce non-equivalent carbon sites and improve the interfacial activity, such that the biphenylene monolayer can be easily oxidized and shows more active carbon sites for chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Such as porous organic compounds, [31] transition metal sulfide (VS 2 , WS 2 , etc. ), [32][33][34] transition metal oxides, [35] metalorganic framework, [36] two-dimensional nanosheets (B 2 C 4 P 2 , B 3 C 2 P 3 ), [37] two-dimensional biphenylene, [38] etc. Studies have shown that these can inhibit the dissolution of polysulfide.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the synthesis of biphenylene (BP) has inspired researchers to pay substantial attention to two-dimensional allotropes of carbon for their tunable electronic, magnetic and catalytic behaviors, as well as their promising application as anchoring materials for batteries. [17][18][19] It has been shown that the BP strips exhibit better thermoelectric properties than graphene and Raman spectroscopy can be used to identify the lattice strain and temperature of BP. 20,21 In this work, we explore the Raman spectra of hydrogen-terminated BP strips of different lengths by using first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%